Lenin, Religion, and Theology - Boer, R. author. aut Link
XII, 347 p.
Keywords: Based on a careful reading of Lenin's Collected Works, Roland Boer pursues the implications for linking Lenin with religion and theology and seeks to bring Lenin into recent debates over the intersections between theology and the Left, between the Bible and political thought.